Inhaled insulin in diabetes management: a review of efficacy, safety, and patient-centered outcomes - Raj, Alwin; Deshpande, Shruti; Hegde, Rashmi; Desai, Anish; Anand, Sunaina (International Journal of Research in Medical Sciences, 2025)
Inhaled insulin offers a non-invasive alternative to subcutaneous insulin for managing diabetes mellitus. Technosphere insulin (TI), marketed as Afrezza, delivers ultra-rapid-acting insulin via the pulmonary route, facilitating rapid absorption and improved post-prandial glucose (PPG) control. Clinical trials have demonstrated that TI achieves non-inferior glycaemic control compared to subcutaneous rapid-acting insulins in both type 1 diabetes mellitus (T1DM) and type 2 diabetes mellitus (T2DM), with notable reductions in HbA1c and enhanced PPG outcomes. TI’s fast onset (peak concentration ~15 minutes) and short duration reduce late hypoglycaemia risk. Studies also report improved patient satisfaction due to greater ease of use and reduced injection burden, supporting better treatment adherence. The most common adverse effect is mild, transient cough; small reversible declines in pulmonary function (FEV1) have been observed, necessitating careful patient selection and monitoring. Inhaled insulin is contraindicated in individuals with chronic lung diseases or recent smoking history. Future research should explore its use in paediatric and pregnant populations and assess long-term safety, adherence, and cost-effectiveness. With expanding evidence from trials like INHALE-3, inhaled insulin represents a valuable addition to the diabetes treatment landscape, particularly for patients seeking flexible and patient-centred insulin therapy.